2021
DOI: 10.7759/cureus.13734
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between High Glycated Hemoglobin and Severity of Coronary Artery Disease in Type II Diabetic Patients Hospitalized With Acute Coronary Syndrome

Abstract: Introduction Diabetes mellitus (DM) is a chronic metabolic disease. It is the principal cause behind the high morbidity and mortality attributed to cardiovascular disease. This article's objective was to determine a connection between high glycated haemoglobin levels (HbA1c) and coronary artery disease (CAD). Materials and Methods Cross-sectional research took place at the lady reading hospital, Peshawar, Pakistan, from 1st July 2020 to 31st December 2020. In this study, one hundred fifty-one type II diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…However, the severity of coronary artery disease was associated with the presence of diabetes, like in our data. Supporting our findings, Khan et al [ 41 ] observed that a high level of HbA1c was associated with an increased severity of coronary artery disease. Our study observed an association between multivessel disease and the presence of diabetes, hypertension, and smoking status.…”
Section: Discussionsupporting
confidence: 91%
“…However, the severity of coronary artery disease was associated with the presence of diabetes, like in our data. Supporting our findings, Khan et al [ 41 ] observed that a high level of HbA1c was associated with an increased severity of coronary artery disease. Our study observed an association between multivessel disease and the presence of diabetes, hypertension, and smoking status.…”
Section: Discussionsupporting
confidence: 91%
“…While in Xu's study, this increase in amount was not seen, and even in some groups with CAD, such as severe obstruction, the amount is lower than that of diabetics without CAD, which was the reason for insulin injection by this group [ 17 ], while in our study, people injecting insulin were excluded from the study. The results of Khan's study in 2021 were completely opposite to Xu's results and the amount of HbA1c in diabetic patients with CAD is more and high HbA1c was related to severe CAD [ 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…A study carried out in Peshawar Lady Reading Hospital in 2020 studied the degree of severity of CAD with HbA1c levels categorizing patients into two groups, namely, poor glycemic control (HbA1c >7.5%) and good glycemic control (HbA1c <7.5%) [14]. The study found a significant association between poor glycemic control and the severity of CAD.…”
Section: Discussionmentioning
confidence: 99%